Systematic Literature Review and Bibliometric Analysis on MSMEs Digitalization Strategies in Indonesia - Yusuf Ramadhan; Roy Darmawan; Nurus Sabani; A. Khoirun Nasihin (Jayapangus Press, 2026)
Research on the digitalization of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia remains dominated by empirical studies, while systematic reviews that map the evolution, structure, and thematic trends of this topic are still limited. Addressing this research gap, this study aims to systematically examine MSME digitalization strategies in Indonesia using a Systematic Literature Review (SLR) combined with bibliometric analysis. The SLR method was applied to articles indexed in the Scopus database for the 2019-2023 period, retrieved through Publish or Perish, and screened based on relevance to the research topic. The bibliometric analysis using VOSviewer was employed to map research trends, identify keyword relationships, and cluster thematic networks within the literature. From an initial pool of 1,000 articles, 80 studies met the inclusion criteria and were analyzed further. The bibliometric visualization identified seven main clusters and three dominant themes, namely digital transformation, MSMEs, and sustainable development. The four most prominent clusters highlighted e-commerce based digitalization strategies, social media utilization for marketing, cloud technology adoption, and digital divide and cybersecurity issues. The findings show that digitalization strategies in Indonesian MSMEs are largely driven by efforts to enhance competitiveness, market expansion, and operational efficiency. Moreover, e-commerce and social media platforms are identified as the dominant drivers of MSME digital transformation. Despite ongoing challenges such as limited technological access and low digital literacy, digitalization continues to yield positive impacts on business performance and sustainability. This study contributes to a clearer understanding of MSME digitalization in Indonesia and provides a comprehensive knowledge base for policymakers and researchers to develop effective digital transformation frameworks.